2001
DOI: 10.3928/0147-7447-20010801-20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Suspected Stress Fractures

Abstract: Stress fractures can occur if normal bone is exposed to repeated abnormal stress (fatigue fractures) or if normal stress is placed on bones with compromised elastic resistance (insufficiency fractures). This article describes two patients without a history of excessive stressful activity or apparent metabolic bone disease who developed bilateral distal tibial stress fractures. Different etiologies, clinical presentation, differential diagnosis, and diagnostic imaging modalities of stress fractures are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…According to previous studies [7], three hard grains mentioned above all appeared in submicron [3] Ti(C,N)-Based cermets, moreover, M.Ehira conducted a TEM+EDX spectrometry analysis to obtain element distribution of these hard grains, and the results were as follows: only Ti was detected in black core grain; W, Mo as well as Ti were detected in white core grain; W, Mo detected in no core grain was less than that in white core grain, while Ti was more in no core grain. As far as the testing results are concerned, these elements have been confirmed via analyzing the dissolution and precipitation process.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…According to previous studies [7], three hard grains mentioned above all appeared in submicron [3] Ti(C,N)-Based cermets, moreover, M.Ehira conducted a TEM+EDX spectrometry analysis to obtain element distribution of these hard grains, and the results were as follows: only Ti was detected in black core grain; W, Mo as well as Ti were detected in white core grain; W, Mo detected in no core grain was less than that in white core grain, while Ti was more in no core grain. As far as the testing results are concerned, these elements have been confirmed via analyzing the dissolution and precipitation process.…”
Section: Discussionmentioning
confidence: 62%
“…Appeared at the end of the past century, nano-science and technology, is developing very quickly as a high and new science and technolog [1,2]. As nano-material [3] possesses high strength, high hardness and excellent ductibility and toughness, more attention has been paid for the application of nano-material. Scientists found that the properties of materials can be improved by adding nano-powder into the conventional materials [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%